Il velo che svela. La traduzione come custode e rivelatrice del segreto letterario - Sofo, Giuseppe (Elephant & Castle, 2019)
Looking at translations as a force that reveals the text gives us the possibility to focus on the hidden meanings within each text, and it allows us to perceive a more complete image of the original in its relationship with its translations, divided only by an invisible and always permeable veil, whose natural movement is its lifting. No veil is made to cover indefinitely, but it is rather a moment of an action that starts with the veiling and ends with the unveiling, only to start again. The translation never covers the original text on the long run, it rather lifts itself to allow access to the text, disappearing while remaining present at the same time. It is this position that allows the translation to become a veil that reveals and safeguards at the same time the “secret” of the literary work, which can only be grasped in its multiplicity, in its perpetual “otherness” which is the product of the constant process of creation and recreation that the translation generates. The veil is therefore no longer an impenetrable frontier, but rather a union of absence and presence, of visibility and invisibility, which leads to a broader understanding of the whole. It is a veil that opens and does not close, that collects to protect and not to hide, revealing hidden aspects of the original text, and safeguarding others.